If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -9y + 7x + 20y = 0 Reorder the terms: 2x + 7x + -9y + 20y = 0 Combine like terms: 2x + 7x = 9x 9x + -9y + 20y = 0 Combine like terms: -9y + 20y = 11y 9x + 11y = 0 Solving 9x + 11y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11y' to each side of the equation. 9x + 11y + -11y = 0 + -11y Combine like terms: 11y + -11y = 0 9x + 0 = 0 + -11y 9x = 0 + -11y Remove the zero: 9x = -11y Divide each side by '9'. x = -1.222222222y Simplifying x = -1.222222222y
| 28x^3+16x^2-80=0 | | C+5/12=19/6 | | 1/3*x+5-(1/6*(2*x-5))=0 | | 10t-6=-2t+1 | | 6-(x+4)=-1+2(x-4) | | 21-x=10 | | 5x-4+6x+1=63 | | 2g+4=2g-21 | | -49*6=7*(a+7) | | 4(4+4x)-(8x-12)=65 | | 32*x-4=4 | | 4(4+4x)-(8x-12)=64 | | 2(n)+n+2=10+n+4 | | 13/6x65/3 | | 15x-106=6x-7 | | 2(.5x+6)=3(x-3) | | 8(x+33)=304 | | -n+19=8n-17 | | 3(2+-2)= | | 4(4+4x)-(8x-12)=80 | | X^2+1.5x-9=0 | | 4x+2y-x-3=0 | | 3(2+d)= | | x-(-8)=-14 | | 2x^2+13+20= | | 0=-24x+39y | | 3(2+-4)= | | 5a-9=6-5a | | 90-2x=16x+22 | | x+(-13)=24 | | x^5/2-2r^3/2=0 | | 13x+9=74 |